Indonesia's protection of Rohingya refugees and regional geopolitical principles - Muttaqin, Entol Zaenal (Lampung Journal of International Law, 2024)
As one of the main countries in the ASEAN regional organisation, Indonesia plays an important role in establishing peace and mutually beneficial relations. Even in the case of the mass exodus of Rohingya refugees, which is attracting attention because it is linked to humanitarian issues, many countries are reluctant to accept the arrival of these refugees who are considered stateless. Moreover, many countries are reluctant to accept the arrival of these refugees who are considered stateless, as Myanmar has revoked their citizenship and does not consider them to be citizens. One of the countries visited is Indonesia, and not just as a country seeking political asylum, but in this case Indonesia is obliged to pay attention, even though legally it has not signed the UN Convention on Refugees, particularly Indonesia's position as a large country within ASEAN. Therefore, this paper aims to answer several questions, namely: the format of Indonesia's policy towards Rohingya asylum seekers under humanitarian and human rights law, then the formula of Indonesia's role in resolving the Rohingya refugee conflict in Myanmar in the context of ASEAN's international relations, and the relevance of Indonesia's international policies and the 1951 Geneva Refugee Convention in protecting refugees across Indonesian borders. The method used is a legal empirical method using primary legal source data and analysed qualitatively. The paper concludes that Indonesia needs to pay attention to the international legal framework regarding refugees, that Indonesia's potential in resolving the Rohingya conflict is very strategic because it is politically active, and finally that the relevance of the 1951 Geneva Convention and Indonesia's foreign policy is very compatible because the convention aims to protect refugees.